Clinical characteristics and treatment outcomes of primary and recurrent malignancy involving the salivary glands in children. Issue 6 (15th July 2015) - Qureshi, Sajid S.; Bhagat, Monica; Singhal, Nitin; Tathe, Nitin; Kembhavi, Seema; Laskar, Siddharth; Ramadwar, Mukta; Yadav, Prabha
Abstract: Background: Malignant salivary gland neoplasms are rare in children. The purpose of this study was to present our experience in the treatment of primary and recurrent salivary gland neoplasm and contribute to the fractional available data. Methods: All patients <18 years, treated between June 2005 and April 2014 were included in this study. Results: The parotid gland was the most common site for both primary ( n = 18) and recurrent ( n = 6) tumors and mucoepidermoid carcinoma, low or intermediate grade, main histological type. Surgical excision was performed in all patients, of which 13 patients received radiotherapy. Lymph node metastasis was present in 3 patients with primary tumor, which were assessed accurately on frozen section examination. Local recurrence occurred in 1 patient with primary tumor and all patients are alive. Conclusion: Surgery is the prime modality of treatment for malignant salivary gland neoplasm and is associated with excellent outcomes. The role of lymph node sampling and frozen section examination needs further evaluation in identifying lymph node metastasis. © 2015 Wiley Periodicals, Inc. Head Neck 38: 852–856, 2016